Animal hunt: bioacoustics animal recognition application - Low, Ren Hwa (Nanyang Technological University, 2024)
This project aims to create a bioacoustics classification model that can be used for real- time identification of animals based on their sounds in mobile applications. The first part of the project will focus on developing a bioacoustics classification model for the backend of the application. The second part of the project will emphasize on the deployment of the model and optimizing its inference performance for edge devices.